A Preliminary Study of Germicidal Efficacy against Candida auris. (4th October 2017) - Rutala, William A; Kanamori, Hajime; Gergen, Maria; Sickbert-Bennett, Emily; Weber, David J
Abstract: Background: Candida auris is an emerging fungal pathogen that is often resistant to major classes of antifungal drugs and can survive on healthcare environmental surfaces, and is now a serious global health threat. It remains unclear whether C . A uris is also resistant to germicides (e.g., disinfectants, antiseptics). In this study, we investigated germicidal activity against C . A uris . Methods: We assessed 21 different germicides plus 2 dilutions of sodium hypochlorite for C . A uris, Candida albicans, and Staphylococcus aureus . The disc-based quantitative carrier testing was performed to evaluate the germicidal activity of chemical germicides. An inoculum containing approximately 10 6 test organisms with 5% fetal calf serum (FCS) was placed on each disk. The dried inoculum was exposed to the test germicide for 1 minute exposure time at room temperature then neutralized. The log10 reduction of the test organism for each biocide was calculated and compared with mean carrier control counts. Results: Efficacy of germicides with active ingredient, product name, and classification against C . A uris, C . A lbicans, and S . A ureus is provided in Figure 1. Our germicidal study demonstrated at least 3-log10 reduction (12/22, 55%) and 2-log10 reduction (15/22, 68%) for C . A uris, 3-log10 reduction (14/22, 64%) and 2-log10 reduction (17/22, 77%) for C . A lbicans, and 3-log10 reduction (22/22, 100%) for S . A ureus in the challenging test conditions (5% FCS and 1 minute exposure time). C . A uris was less susceptible to 0.55% ortho-phthalaldehyde, 2% chlorhexidine gluconate, 4% chlorhexidine gluconate, and 1% chloroxylenol compared with C . A lbicans or S . A ureus . C . A uris was more susceptible to 70% ethanol, compared with C . A lbicans . Several germicides (21.7% quaternary ammonium compounds [QAC], 3% hydrogen peroxide, 5.25% sodium hypochlorite [1:50 dilution], 0.5% triclosan) had <2-log10 reduction for both C . A uris and C . A lbicans . Conclusion: Our preliminary study results suggest that many germicides commonly used in healthcare facilities are effective against C . A uris, but further evaluations are warranted (e.g., QAC, triclosan, chlorhexidine gluconate, hydrogen peroxide) under less challenging test conditions (e.g., without 5% FCS and/or longer exposure time). Disclosures: D. J. Weber, PDI: Consultant, Consulting fee.